ANALYSIS OF THE CULTURAL FACTORS IMPACTS ON THE DEVELOPMENT OF ENTREPRENEURSHIP The Case Study of Garut District - Rida Zuraida; Abdullah Ramdhani; Abdusy Syakur Amin (Universitas Gunadarma, 2009)
Entrepreneurship has been recognized as an important characteristics for the society to accelerate the advancement of their quality of life. Various aspects were identified have significant impact on the development of entrepreneurship such as education, age, culture, etc .In rural area where the population has rather similar low education level, the research tends to focuses on the impact of the cultural aspects on the entrepreneurship will be more appropriate. The research was conducted in the Cilawu and Bayongbong areas which are located in Garut District. 24 respondents which are residents of those areas were withdrawn to fulfill the distributed questionnaire. The research applied Four of Hoffstede’s cultural dimensions to describe inter-culturally comparable aspects, namely (1) individualism vs. collectivism;(2) masculinity vs. Femininit;(3) avoidance of uncertainty, and (4) life orientation on a long term. Research results indicate various differences in the dimensions of avoidance of uncertainty and orientation on a long term. The Cilawu respondents are stronger in avoidance of uncertainty and weaker in long term orientation compared with the Bayongbong respondents. The difference may be caused by natural conditions and number of religious school at each district, thinking pattern, motivation and life goals of both communities. To enable continuous growth of entrepreneurship in both districts, the role of the regional government of the Garut regency is needed to create a conducive socio-cultural environment by observing the cultural aspects which have the potential of creating the trend of entrepreneurship in each district.Keywords : entrepreneurship, Hoffstede’s cultural dimensions, Garut